Retrospective analysis of antimicrobial susceptibility trends (2000-2009) in Neisseria gonorrhoeae isolates from countries in Latin America and the Caribbean shows evolving resistance to ciprofloxacin, azithromycin and decreased susceptibility to ceftriaxone - Starnino, Stefania (2012)
Fil: Starnino, Stefania. Vaccine and Infectious Diseases Organization, University of Saskatchewan, Saskatoon, Saskatchewan; Canada.